Attitudes of Black American Christian church leaders toward Opioid Use Disorder, overdoses, and harm reduction: a qualitative study - Dankwah, Akosua B.; Siegrist, Richard B.; Wilson, Ira B.; McKenzie, Michelle; Rich, Josiah D. (Frontiers in Psychiatry, 2024)
Introduction: Black American Christian church leaders are trusted community members and can be invaluable leaders and planners, listeners, and counselors for Opioid Use Disorder (OUD) sufferers in the opioid overdose crisis disproportionately affecting the Black community. This qualitative study examines the extent to which the knowledge, attitudes, practices, and beliefs of Black American church leaders support medical and harm reduction interventions for people with OUD. Methods: A semi-structured interview guide was used to conduct in-depth interviews of 30 Black Rhode Island church leaders recruited by convenience and snowball sampling. Results: Thematic analysis of the interviews identified four themes: Church leaders are empathetic and knowledgeable, believe that hopelessness and inequity are OUD risk factors, are committed to helping people flourish beyond staying alive, and welcome collaborations between church and state. Discussion: While the Black American church leaders are concerned about interventions they perceive as perpetuating use, such as fentanyl test strips or sterile syringe exchanges, they are open to many harm reduction interventions, including counseling, Medications for Opioid Use Disorder, and naloxone. Conclusion: They Black American Christian church leaders are a critical resource in providing innovative and culturally sensitive strategies in the opioid overdose crisis affecting the Black American communities. As such, their views should be carefully considered in OUD policies, collaborations, and interventions in the Black American community.